2018
DOI: 10.1002/mbo3.672
|View full text |Cite
|
Sign up to set email alerts
|

Succession of embryonic and the intestinal bacterial communities of Atlantic salmon (Salmo salar) reveals stage‐specific microbial signatures

Abstract: Host-associated microbiota undergoes a continuous transition, from the birth to adulthood of the host. These developmental stage-related transitions could lead to specific microbial signatures that could impact the host biological processes. In this study, the succession of early-life and intestinal bacterial communities of Atlantic salmon (starting from embryonic stages to 80-week post hatch; wph) was studied using amplicon sequencing of 16S rRNA. Stage-specific bacterial community compositions and the progre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
85
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 69 publications
12
85
1
3
Order By: Relevance
“…Outside of the core microbiome, the composition of the bacterial community varied between each stage. Stage‐specific bacterial communities have also been observed for other fish and are thought to result from to a combination of stochastic and deterministic processes (Ingerslev et al ., ; Burns et al ., ; Yan et al ., ; Lokesh et al ., ). With respect to the S. lalandi investigated here, the most substantial gut microbiome changes occurred as the larvae transitioned from live feeds to the formulated pellet, suggesting that the temporal variation observed in this study was likely due to the changing diet.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Outside of the core microbiome, the composition of the bacterial community varied between each stage. Stage‐specific bacterial communities have also been observed for other fish and are thought to result from to a combination of stochastic and deterministic processes (Ingerslev et al ., ; Burns et al ., ; Yan et al ., ; Lokesh et al ., ). With respect to the S. lalandi investigated here, the most substantial gut microbiome changes occurred as the larvae transitioned from live feeds to the formulated pellet, suggesting that the temporal variation observed in this study was likely due to the changing diet.…”
Section: Discussionmentioning
confidence: 97%
“…While environmental contamination cannot be ruled out, it is plausible that these bacteria represent early egg colonizers that have remained despite ozone sterilization prior to entering the hatchery facility. Indeed, several studies have shown early colonization of newly released eggs (Lauzon et al, 2010;Llewellyn et al, 2014;Lokesh et al, 2018). Future investigation of the microbial community associated with the fertilized eggs and the broodstock environment will be necessary to determine the true source of these early S. lalandi microbiome members.…”
Section: Discussionmentioning
confidence: 99%
“…For example, environmental stress or antibiotic treatment which disturbs the microbiome may allow resistant taxa to flourish in the absence of wider competition, delaying the restoration of the original complex community (Foster, Rinaman, & Cryan, ; Yassour et al, ). As observed in mammals, the microbial composition of fish is particularly dynamic during early development, as it is readily influenced by variation in the surrounding environment, host immunity and microbial seeding communities (Giatsis et al, ; Korpela et al, ; Lokesh, Kiron, Sipkema, Fernandes, & Moum, ; Stephens et al, ; Yan et al, ). This suggests that historical effects on microbiome structure due to environmental variation during early life may be particularly important (Gensollen, Iyer, Kasper, & Blumberg, ; Martínez et al, ; Sprockett et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Once established, these taxa are then likely to have had an enhanced ability to out-compete subsequent colonisers and retain their dominant position through niche pre-emption (Sprockett et al 2018; Walter & Ley 2011). It could be that these colonisation effects remained more pronounced and consistent in the skin microbiome because gut microbial communities are subsequently more readily influenced by the diet (Ingerslev et al 2014; Lokesh et al 2019).…”
Section: Discussionmentioning
confidence: 99%